Investigation of oxidized triglyceride monomer (oxTGM) produced in deteriorated soybean oil at frying temperatures: A kinetic study. (December 2022) - Li, Xu; Wang, Zhisheng; Xing, Changming; Chen, Zike; Sun, Wenxing; Xie, Dan; Xu, Guangfei; Wang, Xingguo
Graphical abstract: Highlights: Two characteristic kinetic times by turning and intersection methods were compared. Accumulation of oxidized triglycerides is 2.35%-12.35% earlier than oxidized fatty acids. oxTGM accumulates earlier than observed PV for edible oils heated at 90 °C-170 °C. oxTGM in TPC can be a better indicator to monitor thermo-oxidation of edible oil. Abstract: This work evaluated the feasibility of total polar compound (TPC) and its five components to monitor the deterioration of soybean oil at frying temperatures, and traditional indicators were used as a reference. The preliminary correlation analysis showed that polar compounds accumulated earlier than classical oxidation products like the peroxide value (PV). Equations for two types of characteristic kinetic time, the induction time (turning point of sigmoid curve) and intersection time (intersection point of two tangent lines representing the initiation and propagation reaction), were also derived. Their mathematical difference and relationship were then evaluated. Based on the kinetic analysis, the overall cumulative process of oxidation products of triglycerides (oxTGM) was found to be 2.35%-12.35% earlier than that of fatty acids (PV). Our results supported the index of oxTGM in TPC to be a better indicator to monitor the deterioration of heated edible oil.